Non-invasive imaging software to assess the functional significance of coronary stenoses: a systematic review and economic evaluation - Ana Duarte; Alexis Llewellyn; Ruth Walker; Laetitia Schmitt; Kath Wright; Simon Walker; Claire Rothery; Mark Simmonds (Health Technology Assessment, 2021)
Background: QAngio® XA 3D/QFR® (three-dimensional/quantitative flow ratio) imaging software (Medis Medical Imaging Systems BV, Leiden, the Netherlands) and CAAS® vFFR® (vessel fractional flow reserve) imaging software (Pie Medical Imaging BV, Maastricht, the Netherlands) are non-invasive technologies to assess the functional significance of coronary stenoses, which can be alternatives to invasive fractional flow reserve assessment. Objectives: The objectives were to determine the clinical effectiveness and cost-effectiveness of QAngio XA 3D/QFR and CAAS vFFR. Methods: We performed a systematic review of all evidence on QAngio XA 3D/QFR and CAAS vFFR, including diagnostic accuracy, clinical effectiveness, implementation and economic analyses. We searched MEDLINE and other databases to January 2020 for studies where either technology was used and compared with fractional flow reserve in patients with intermediate stenosis. The risk of bias was assessed with quality assessment of diagnostic accuracy studies. Meta-analyses of diagnostic accuracy were performed. Clinical and implementation outcomes were synthesised narratively. A simulation study investigated the clinical impact of using QAngio XA 3D/QFR. We developed a de novo decision-analytic model to estimate the cost-effectiveness of QAngio XA 3D/QFR and CAAS vFFR relative to invasive fractional flow reserve or invasive coronary angiography alone. Scenario analyses were undertaken to explore the robustness of the results to variation in the sources of data used to populate the model and alternative assumptions. Results: Thirty-nine studies (5440 patients) of QAngio XA 3D/QFR and three studies (500 patients) of CAAS vFFR were included. QAngio XA 3D/QFR had good diagnostic accuracy to predict functionally significant fractional flow reserve (≤ 0.80 cut-off point); contrast-flow quantitative flow ratio had a sensitivity of 85% (95% confidence interval 78% to 90%) and a specificity of 91% (95% confidence interval 85% to 95%). A total of 95% of quantitative flow ratio measurements were within 0.14 of the fractional flow reserve. Data on the diagnostic accuracy of CAAS vFFR were limited and a full meta-analysis was not feasible. There were very few data on clinical and implementation outcomes. The simulation found that quantitative flow ratio slightly increased the revascularisation rate when compared with fractional flow reserve, from 40.2% to 42.0%. Quantitative flow ratio and fractional flow reserve resulted in similar numbers of subsequent coronary events. The base-case cost-effectiveness results showed that the test strategy with the highest net benefit was invasive coronary angiography with confirmatory fractional flow reserve. The next best strategies were QAngio XA 3D/QFR and CAAS vFFR (without fractional flow reserve). However, the difference in net benefit between this best strategy and the next best was small, ranging from 0.007 to 0.012 quality-adjusted life-years (or equivalently £140–240) per patient diagnosed at a cost-effectiveness threshold of £20,000 per quality-adjusted life-year. Limitations: Diagnostic accuracy evidence on CAAS vFFR, and evidence on the clinical impact of QAngio XA 3D/QFR, were limited. Conclusions: Quantitative flow ratio as measured by QAngio XA 3D/QFR has good agreement and diagnostic accuracy compared with fractional flow reserve and is preferable to standard invasive coronary angiography alone. It appears to have very similar cost-effectiveness to fractional flow reserve and, therefore, pending further evidence on general clinical benefits and specific subgroups, could be a reasonable alternative. The clinical effectiveness and cost-effectiveness of CAAS vFFR are uncertain. Randomised controlled trial evidence evaluating the effect of quantitative flow ratio on clinical and patient-centred outcomes is needed. Future work: Studies are required to assess the diagnostic accuracy and clinical feasibility of CAAS vFFR. Large ongoing randomised trials will hopefully inform the clinical value of QAngio XA 3D/QFR. Study registration: This study is registered as PROSPERO CRD42019154575. Funding: This project was funded by the National Institute for Health Research (NIHR) Evidence Synthesis programme and will be published in full in Health Technology Assessment; Vol. 25, No. 56. See the NIHR Journals Library website for further project information.